3PC-060 Physicochemical stability of vancomycin solution in elastomeric devices at 37.5 mg/mL in 0.9% sodium chloride and dextrose 5% in water. (14th March 2021) - Polo, C; D'huart, E; Vigneron, J; Charmillon, A; Demore, B
Abstract : Background and importance: Vancomycin is a time dependent antibiotic of the glycopeptide family. The recommended dose of vancomycin is 30–40 mg/kg/day. For an adult, the maximum daily dose can reach 4 g. In clinical practice, vancomycin is mostly administered by continuous infusion. After hospitalisation, administration of concentrated solutions in elastomeric devices would allow a home care service and a better quality of life for the patient. Aim and objectives: The objective of this work was to study the stability of vancomycin solutions at 37.5 mg/mL (4.5 g in 120 mL of solvent) diluted in 0.9% sodium chloride (0.9% NaCl) or in dextrose 5% in water (D5W), in elastomeric devices, protected from light, at 37°C for 48 hours. Material and methods: Chemical stability was analysed by high performance liquid chromatography coupled to a photodiode array detector and by pH measurements after preparation, after 24 hours and 48 hours of storage. The method was validated according to the International Conference on Harmonisation Q2 (R1). Three elastomeric devices for each condition were prepared. Physical stability was evaluated by a visual and subvisual inspection at each time of analysis (turbidimetry by UV spectrophotometry at three wavelengths: 350, 410 and 550 nm). Results: For each solvent, solutions at 37.5 mg/mL retained more than 90% of the initial concentration for 48 hours: for 0.9% NaCl (minimum 96.49%±1.12%; maximum 100.94%±0.51%) and for D5W (minimum 102.75%±1.19%; maximum 104.67%±1.15%). During the study, pH values did not decrease after 48 hours in the two solvents. During the subvisual examination, there was no significant difference between the different analysis times regardless of the solvent used. No colour change was reported during the study. Conclusion and relevance: Vancomycin solutions at 37.5 mg/mL in 0.9% NaCl and D5W were stable in elastomeric devices for 48 hours at 37°C, protected from light. Home administration for this concentration is possible. References and/or acknowledgements: Conflict of interest: No conflict of interest